Pengembangan Bahan Ajar Interaktif Berbasis Artificial Intelligence dalam Mendukung Pembelajaran Diferensiasi pada Fase B - Irmawati M; Muflihah Baktiar; Putri Indriani; Muh. Irham Nugraha (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
This research aims to develop interactive teaching materials based on Artificial Intelligence (AI) that can support the application of differentiated learning in Phase B students. This research uses a Research and Development (R&D) approach with a 4D (Define, Design, Develop, Disseminate) development model. Validation was carried out on three main components, namely teaching materials, learning outcome instruments, and teacher and student response questionnaires. The validation results showed that the teaching materials obtained an average score of 3.7 and were declared very valid, both in terms of content, display, and language use. The learning outcome instruments validated from the aspects of questions, construction, language, and time allocation also obtained an average of 3.7. The teacher and student response questionnaires achieved an average of 3.8 and 3.9, respectively, which indicates high feasibility in exploring user perceptions. The limited trial showed a positive response from all teachers and students (100%). These findings show that AI-based interactive teaching materials are feasible and have the potential to be an effective and responsive learning tool to student needs in the context of differentiated learning.